Evaluating Biological Risks in Biomedical Laboratories of Primary Health Care - Vourtsis, Dionysios; Papageorgiou, Efstathia; Kriebardis, Anastasios; van Willigen, Gijsbert; Kotrokois, Kostas; Karkalousos, Petros (European Scientific Journal, ESJ, 2025)
Biomedical laboratories within primary health care centers are vital for the detection, diagnosis, and management of diseases. However, handling diagnostic samples poses significant biological risks, particularly when biosafety measures are insufficient. This study focuses on analyzing the biological risks in 35 BSL-2 biomedical laboratories situated in health facilities across Athens, Greece, by examining compliance with biosafety regulations, awareness of personnel safety, and practices related to biorisk management. A cross-sectional survey was conducted by combining a customized checklist and a structured health and safety questionnaire, both have been created from the existing literature including the international biosafety guidelines (BMBL 6th ed., WHO Biosafety Program Management, 2020). An expert biorisk management advisor performed on-site evaluations, while 158 laboratory staff members filled out anonymous questionnaires concerning biosafety practices. Findings indicate widespread deficiencies in biosafety culture and risk management. Key gaps were identified in engineering controls (such as restricted access and safety equipment), administrative controls (including risk assessments, standard operating procedures, biosafety manuals, biosafety officers, and ongoing training), personal protective equipment (PPE policies), and emergency preparedness (such as incident reporting, response plans, and occupational health services). Many laboratories failed to meet international biosafety standards set by the WHO, CDC, and ECDC, highlighting the need for urgent improvements. To mitigate these risks, the study recommends the adoption of comprehensive Biorisk Management Systems, enhanced biosafety training, and stricter enforcement of national and European biosafety regulations. Strengthening these measures is essential to protect the laboratory staff, the surrounding community, and the environment from potential biological threats and lab-acquired infections.